The right to life and the beginning of human life - Peyrano, Guillermo F. (2021)
The revelations that scientific and technical advances are constantly occurring in the fields of biology, medicine and gene tics, in all matters relating to starting and generation of human life, have decisive impact on legal solutions applicable to the. se problems, and have reached crisis put many centuries accepted truths. At this time the questions and doubts are multiplied by direct impact of the results that we provide research in constant development, Researchers try to uncover the most pressing unknowns, and work trying to find the most appropriate answers to questions such as: From what moment can be argued that there is life ?, for human life when it starts ?, from what time or stage embryonic development should be recognized the right to life and personality of the embryo ?, human life, human beings and human beings, are matching terms? Possible answers to these questions have a capital importance, since they are involved in them, not only biological and legal, but also moral and religious issues. To address these problems, and provide feedback based on their context, will seek to analyze from different perspectives, sought to avail ourselves of new insights provided by scientific and technical advances. We caution that such knowledge may not be sufficient to obtain fully satisfactory answers.